Parental phubbing and smartphone addiction in adolescents: A meta-analysis review - Marini, Liza; Hendriani, Wiwin; Wulandari, Primatia (Universitas Mercu Buana Yogyakarta, 2023)
Few studies have found that parental phubbing is a vital precursor of adolescents’ problematic smartphone use (smartphone addiction). This meta-analysis uses seven studies selected from multiple electronic databases, namely Scopus, Web of Science, Science Direct, and Google Scholar resulting in a total sample of 6,908 participants, in order to determine how strong the relationship between parental phubbing and smartphone addiction is in adolescents. The literature search was conducted from May 25 to 26 of 2022, limiting it to reputable journals published in English within the last 10 years from 2012 to 2021. The data analysis and the article quality assessment conducted using the Mix Methods Appraisal Tool (MMAT) and Jamovi. The results of the meta-analysis indicate a high level of heterogeneity (89.77%), but no publication bias was found. This heterogeneity is caused by, among other things, the small number of studies, the high variations in the characteristics of the respondents, and differences in research methodologies. This study finds that parental phubbing has a medium positive correlation, i.e. r= 0.32, 95% CI = 0.241 – 0.392. Therefore, it can be concluded that parental phubbing is not the only factor that influences smartphone addiction in adolescents. Hence, future researchers can include other variables that might influence the relationship between parental phubbing and smartphone addiction in adolescents.